ON THE NATURAL-SCIENTIFIC METHODS OF RESEARCH IN ECONOMICS - V. Lebedev; K. Lebedev (Вестник университета)
The new directions of the economics, associated with the use of natural-scientific methods are discussed. The conclusion is justified that the development of these areas is aimed at strengthening the adequacy of mathematical models and fosters a general social analysis.